Plasmon energy and microhardness of BxAl1-xSb alloys: semi-empirical prediction - Mezouar, Rabie; Logzit, Nacer (International Journal of Physical Research, 2023)
Based on the reflective index reported in the literature, the present work aims to investigate the plasmon energy, the microhardness and the homopolar band gap energy of BxAl1-xSb ternary semiconducting alloys as a function of boron concentration x in the range 0 –1. We found that both the plasmon energy and the microhardness of BxAl1-xSb alloys change gradually but not monotonically with increasing of boron concentration x from 0 to 1, while the homopolar band gap energy increases monotonically with enhancing of x. We emphasize that a boron concentration x dependent plasmon energy and microhardness between 0 and 1 is extremely unusual behavior for BxAl1-xSb alloys. Normally, both plasmon energy and the microhardness monotonically increase with increasing boron concentration x as it was mentioned in the literature. The plasmon energy of AlSb and BSb was found to be 16.14 and 15.58 eV, respectively. Our value (16.14 eV) of the plasmon energy for AlSb compound is higher than the result (13.8 eV) reported by Böer and Pohl. The minimum of the plasmon energy was found to be 14.4 eV for both B0.5Al0.5Sb and B0.625Al0.375Sb alloys. The microhardness of AlSb was found at around 7.56 GPa, while that of BSb was found to be 6.51 GPa. Similar to the plasmon energy, the minimum value of the microhardness was found to be 4.45 GPa for both B0.5Al0.5Sb and B0.625Al0.375Sb alloys.